Konstruksi Media Terhadap Berita Kasus Penistaan Agama Oleh Basuki Tjahaja Purnama (Ahok): Analisis Framing Pada Surat Kabar Kompas dan Republik - Silvina Mayasari (Universitas Bina Sarana Informatika, 2017)
Religion is an important object of the news that has high political social effects, it is not independent ofthe position and the level of understanding of religion common to the community. This favorable position to encourage the mass media to consistently allocate space for preaching religious issues. The theory used is the theory of social construction of Peter L. Berger and Thomas Luckman which became known as the